2019
DOI: 10.3389/fninf.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of the Hippocampal Subfields Atrophy in the Alzheimer’s Disease: A Structural Imaging Study

Abstract: Background The hippocampus and hippocampal subfields have been found to be diversely affected in Alzheimer’s Disease (AD) and early stages of Alzheimer’s disease by neuroimaging studies. However, our knowledge is still lacking about the trajectories of the hippocampus and hippocampal subfields atrophy with the progression of Alzheimer’s disease. Objective To identify which subfields of the hippocampus differ in the trajectories of Alzheimer’s disease by magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
74
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 45 publications
22
74
2
2
Order By: Relevance
“…Our results were supported by previous studies, which reported that the subiculum and CA1 related with cognition in T2DM rat and human [38,43,44]. A structural imaging study in patients with subjective cognitive decline found volume reductions in the presubiculum, molecular layer and fimbria [19]. Another study in a large population-based cohort reported smaller volumes of the hippocampal fimbria, presubiculum and subiculum that was related to a risk of dementia [45].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were supported by previous studies, which reported that the subiculum and CA1 related with cognition in T2DM rat and human [38,43,44]. A structural imaging study in patients with subjective cognitive decline found volume reductions in the presubiculum, molecular layer and fimbria [19]. Another study in a large population-based cohort reported smaller volumes of the hippocampal fimbria, presubiculum and subiculum that was related to a risk of dementia [45].…”
Section: Discussionsupporting
confidence: 91%
“…Free-Surfer is a freely available voxel-based software package that provides extensive and automated neuroimaging analysis [15]. Compared with manual segmentation, FreeSurfer is highly efficient, accurate [16,17], and has been successfully used to precisely segment the hippocampus [18][19][20][21]. A recent study in AD patients found that atrophy of the left subiculum correlated with cognitive disorders [19].…”
Section: Introductionmentioning
confidence: 99%
“…These neurotoxicological data collectively suggest that some hippocampal subfields may be more sensitive than others to the adverse PM-effects. Additionally, human imaging studies (Zhao et al, 2019) have found that atrophy in hippocampal subfields imposed varying degrees of influences on different measures of episodic memory (immediate recalls; delayed-recalls; recognition). Previous research also suggests that the CA2, CA3, and dentate gyrus are responsible for encoding, while the CA1 and subiculum are responsible for retrieval (Zammit et al, 2017).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…For example, decreased amyloid beta protein 42 (Aβ-42) and elevated tau level in CSF were found in patients with SCD (Visser et al, 2009). SCD patients also tend to present AD/aMCI-like gray matter atrophy, decreased metabolism, and increased amyloid load, especially in the hippocampus Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%